Evaluating post-Covid-19 Curriculum at Mi Nurussalam Ngawi: Enablers and Barriers - Muhammad Thoriqul Islam; Nurdiyanto Nurdiyanto; Nawa Marjany; Khoula Azwary; Safiruddin Al Baqi; Umaimah ' Affaf (Syntax Corporation Indonesia, 2024)
The main challenge after COVID-19 is the implementation of the new normal era in education, where schools are faced with a choice of three curricula: the 2013 Curriculum, the Emergency Curriculum (simplified from the 2013 Curriculum), and the Prototype Curriculum. The research focuses on post-Covid-19 pandemic curriculum analysis at MI Nurussalam, Ngawi, and supports and inhibits factors for its implementation. This research uses qualitative research methods and a case study approach. Data collection techniques involve observation, interviews, and documentation studies. The research results show that MI Nurussalam, Ngawi chose to implement the 2013 Curriculum, considering that the curriculum had been implemented before the pandemic. Supporting factors for implementing the 2013 Curriculum during the recovery period include the role of teachers as indicators of learning implementation, the use of online learning tools, and exciting learning methods. However, the inhibiting factors involve a need for more cooperation between teachers and guardians, a lack of facilities and infrastructure to support learning, and student motivation at the madrasah and at home.